Integrating Islamic Social Finance and Islamic Fintech for Household Financial Resilience in Indonesia - Muhammad Yusuf Bahtiar (Athallah Publishing Globalindo, 2025)
This conceptual paper explores how the integration of Islamic social finance (ISF) zakat, infaq, ṣadaqah and waqf with Islamic financial technology (Islamic fintech) can strengthen household financial resilience in Indonesia. Although Indonesia has a large Muslim population and strong potential of zakat and waqf actual collection remains far below its potential, and many Muslim households are still vulnerable to income shocks, limited savings buffers and reliance on informal debt. At the same time rapid growth of digital zakat platforms and Islamic fintech solutions such as peer to peer (P2P) financing, sharia compliant crowdfunding, and digital payment channels has opened new opportunities for inclusive, technology enabled Islamic finance. However existing studies tend to examine digital zakat adoption and Islamic fintech for financial inclusion separately with limited attention to household resilience outcomes and to the design of an integrated ecosystem. Using an integrative literature review this paper synthesizes recent findings on ISF, Islamic fintech and financial resilience from an Islamic economics perspective. It then proposes a three layer integration model: (1) digital safety nets through ISF for consumption smoothing; (2) sharia compliant productive financing for asset building; and (3) risk protection instruments (micro takāful and emergency funds) supported by digital infrastructure and data analytics. The model is anchored in maqāṣid al-sharīʿah, especially preservation and fair circulation of wealth (ḥifẓ al-māl), and offers practical implications for regulators, Islamic financial institutions and zakat waqf organizations in Indonesia.